Echoes Of Freedom In Julia Alvarez’s In The Name Of Salome: A Narrative Exploration - C. Abinaya; Dr. K. Ashok Kumar (Revista Electronica de Veterinaria, 1970)
Julia Alvarez’s In the Name of Salome explore the themes of identity, history, and liberation by examining the intertwined lives of two women, Salome Urena, a Dominican poet, who is struggling to understand herself and her daughter Camila, who struggle to discover her own identity. The story examines the impact of personal and national histories on the search for self-realization, with particular attention paid to Salome’s decision to use her poetry in support of patriotic movements and Camila’s journey of self-analyzes during her time of exiled. The paper also delves into the difficulties associated with traditional gender roles, highlighting how these women confront the constraints of a patriarchal society in their pursuit of personal and political autonomy.